Pengaruh Perjanjian Perdagangan Regional Terhadap Volatilitas Pasar Keuangan di Negara Berkembang: Studi Empiris Asia Tenggara - Kusniawati, Amelia; Putri, Adistie Prestiani; Riyadi, Slamet (ARBITRASE: Journal of Economics and Accounting, 2025)
Regional Trade Agreements (RTAs) such as ASEAN and the Regional Comprehensive Economic Partnership (RCEP) have become major drivers of economic integration in the Southeast Asian region. For developing countries, participation in RTAs has complex implications for financial market stability, particularly through its effects on stock market volatility, exchange rate fluctuations, and cross-border capital flows. This study aims to systematically examine how ASEAN countries’ involvement in RTAs affects domestic financial market dynamics, focusing on medium-term volatility and stability components. The method used is the Systematic Literature Review (SLR) by examining published scientific literature from various national and international databases. The review results show that the impact of RTAs on stock markets and currencies tends to vary depending on macroeconomic conditions, institutional capacity, and capital flow management policies in each country. Several studies conclude that RCEP can increase market confidence and strengthen financial integration, while other studies reveal the potential for increased volatility due to financial liberalization that has not been balanced by the strengthening of domestic supervisory systems. These findings emphasize the importance of designing responsive economic policies to maximize the benefits of RTAs while maintaining national financial stability.